OPTIMISTIC SENSES OF TEACHING AT HIGHER SCHOOL - A. S. ROBOTOVA (Высшее образование в России)
The paper presents a general view on the problems of teaching at higher school. The author substantiates her personal understanding of teacher’s activities sense, based on her own teaching experience at school, lyceum, and university and the retrospective reflection of her own activities. Spiritual crisis that education faces now, blurring of boundaries of pedagogy as a science, imperfectness and unproductivity of dominating ideas, innumerable approaches and turns in pedagogy – all these factors do not excuse traditionalism and conservatism in pedagogy as well as thoughtless using of untested innovations. One of the problems of modern pedagogy is its linearity which doesn’t permit to understand pupils and students. In spite of these factors, the paper accentuates the optimistic sense of teacher’s activities. There are multiple sources of such optimistic approach. They are in the emotional awareness of the ultimate value and aim of teacher’s work, in the joy of cognition of another man, in the transformation of students’ personalities.